1999
DOI: 10.1021/bi990351u
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA Primase:  Anion Inhibition, Manganese Stimulation, and Their Effects on In Vitro Start-Site Selection

Abstract: We examined the effects of Mn(2+) on eukaryotic DNA primase both in the presence and absence of 5 mM Mg(2+). In the absence of Mg(2+), Mn(2+)-supported primase activity to a level 4-fold greater than that obtained with Mg(2+) alone, and adding low levels of Mn(2+) (100 microM) to assays containing 5 mM Mg(2+) greatly stimulated primase. Increased activity was primarily due to more efficient utilization of NTPs, as reflected in a lower K(M) for NTPs. Under conditions of saturating NTPs, Mn(2+) had minimal effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…The same dependence has been observed for the human DNA primase: it was shown that Mn 2+ binds and stimulates the primase by decreasing the K m value for NTPs. 27 Thus, the determination of the intracellular composition in Archaea would be extremely useful in understanding the in vivo activities of the archaeal DNA primase and would contribute to understanding more precisely the length and composition of the primers synthesized. It is also possible that, in vivo, other factors are required to modulate the synthesis capability of the DNA primase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same dependence has been observed for the human DNA primase: it was shown that Mn 2+ binds and stimulates the primase by decreasing the K m value for NTPs. 27 Thus, the determination of the intracellular composition in Archaea would be extremely useful in understanding the in vivo activities of the archaeal DNA primase and would contribute to understanding more precisely the length and composition of the primers synthesized. It is also possible that, in vivo, other factors are required to modulate the synthesis capability of the DNA primase.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the optimal conditions fixed for measuring dNTP incorporation were insufficient to detect NTP incorporation. Because the presence of manganese improves NTP incorporation of the archaeal and eukaryotic primases, 13,17,[27][28][29] we studied the influence of Mn 2+ and Mg 2+ concentrations on RNA synthesis capability. Increased MgCl 2 concentrations only slightly enhanced NTP incorporation, in contrast to MnCl 2 (Fig.…”
Section: Rna Synthesis Capability Of the Pab Dna Primasementioning
confidence: 99%
“…Eukaryal DNA primase is optimally active in the presence of manganese (15) and displays an exceptionally high rate of nucleotide misincorporation during templated RNA synthesis (16 -19). Archaeal DNA primase, too, is optimally active in the presence of manganese (20 -22).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that eukaryotic primase preferentially initiates within pyrimidine-rich sequences (3,32,35,40,44,71,85,89). In order for primase to initiate DNA synthesis, a stable complex must form between primase and the pyrimidine-rich initiation sites.…”
Section: Discussionmentioning
confidence: 99%